Letter from Max Bredig to Marianne and Viktor Homburger, May 8, 1940 - Bredig, Max Albert (1940)
Max Bredig (1902-1977) informs his sister, Marianne Homburger (1903-1987), and his brother-in-law, Viktor Homburger (1888-1968), that he is sending them a new affidavit for the purpose of immigrating to the United States.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Jewish Holocaust (1939-1945); Emigration and immigration